Clinical effectiveness of customized versus noncustomized orthodontic appliances: A systematic review - Yassir A. Yassir; Mostafa K. Sofar; Grant T. McIntyre; David R. Bearn (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVE: To evaluate the clinical effectiveness of treatment with customized compared to noncustomized fixed orthodontic appliances. METHOD: A comprehensive search was performed using 13 databases until February 20, 2024. Study eligibility criteria were based on studies that compared orthodontic treatment with customized fixed appliances (labial or lingual) with noncustomized appliances. All ages and types of malocclusions were included. RESULTS: The search identified 95 studies, of which only four fulfilled the inclusion criteria. Three studies compared labial customized brackets with self-ligating brackets, while one study compared lingual customized brackets with labial conventional brackets. There were no significant differences between these systems for treatment duration, outcome, number of appointments, analgesic consumption, patient satisfaction, and the archwire bends requirement. On the other hand, treatment planning was longer and the finishing and detailing phase was shorter in the customized appliances. There was a greater tendency for mandibular incisor proclination and bracket repositioning in the noncustomized appliances group and a greater number of bracket failures, complaints, and requirements for archwire changes in the customized appliances. Qualitative synthesis was applied due to heterogeneity in investigating the difference between the two appliance systems. CONCLUSION: Based on the current limited evidence, the clinical effectiveness of customized and noncustomized orthodontic appliances was similar for the majority of clinical outcomes. Further high-quality clinical studies are required to confirm this finding. CLINICAL RELEVANCE: Proper treatment planning and clinical management are the key factors for adequate outcomes apart from the type of appliance used.